2018
DOI: 10.22441/mix.2018.v8i2.001
|View full text |Cite
|
Sign up to set email alerts
|

Minat Pemilihan Perguruan Tinggi Dan Peran Kelompok Referensi Serta Komunikasi Pemasaran Terintegrasi

Abstract: Abstract. This study aims to examine the role of reference groups and integrated marketing communications with the intention of college selection through the mediation of attitudes and subjective norms of consumers. The analysis is done from the perspective of high school students in Indonesia as a developing country. The survey was conducted on 432 students with 91.90 percent of respondent's data that can be analyzed. Data analysis and model testing are proposed using Structural Equation Modeling - Lisrel. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…The results of this study are supported by the results of research conducted by (Muntadliroh, 2016) found that the implementation of an integrated marketing communication strategy for ecotourism services at the Eka Karya Bali Botanical Gardens has a significant impact on increasing tourist interest in visiting the Eka Karya Bali Botanical Gardens. Interest in choosing a college is influenced by integrated marketing communications, reference groups, attitudes, and subjective norms of prospective students (Harwani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are supported by the results of research conducted by (Muntadliroh, 2016) found that the implementation of an integrated marketing communication strategy for ecotourism services at the Eka Karya Bali Botanical Gardens has a significant impact on increasing tourist interest in visiting the Eka Karya Bali Botanical Gardens. Interest in choosing a college is influenced by integrated marketing communications, reference groups, attitudes, and subjective norms of prospective students (Harwani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Someone who has an interest in an activity will do the activity with pleasure, Sintya (2019). While Harwani (2018) expressed Intention, which is a statement of individual attitudes regarding how to behave in the future. While Khairani (2017) states that "Interest is different from talent, interest arises from familiarization with the environment or the results of interacting and learning with the environment".…”
Section: Literature Review 1 Entrepreneurial Intentionmentioning
confidence: 99%
“…Keinginan masyarakat untuk melanjutkan ke pendidikan tinggi sangatlah besar dan menjadi sorotan untuk dijadikan penelitian demi membentuk strategi guna menarik mahasiswa ke perguruan tinggi sesuai dengan disiplin ilmu yang ditawarkan (Bakker et al, 2019;Harwani et al, 2018;Miguel & Tambe, 2021). Sehubungan dengan ini, Lembaga pusat pembelajaran pendidikan tinggi atau disebut Perguruan Tinggi tidak hanya menyediakan kebutuhan dan mengelola kualitas pendidikan tinggi, tapi juga saling berlomba untuk menunjukkan mutu yang baik agar diminati (Kartikasari et al, 2018;Simangunsong, 2019).…”
Section: Pendahuluanunclassified